The ε_∞-product of a b-space by a quotient bornological space - Aqzzouz, B. (Methods of Functional Analysis and Topology, 2007)
We define the ε_∞ -product of a Banach space G by a quotient bornological space EF that we denote by Gε _∞ (EF), and we prove that G is an % L_∞ -space if and only if the quotient bornological spaces Gε _∞ (EF) and % (Gε E)(Gε F) are isomorphic. Also, we show that the functor .ε _∞ .:Ban× qBanqBan is left exact. Finally, we define the ε _∞ -product of a b-space by a quotient bornological space and we prove that if G is an % ε b-space and EF is a quotient bornological space, then (Gε E)(Gε F) is isomorphic to Gε _∞ (EF).